Movement disorder society criteria for clinically established early Parkinson's disease. Issue 10 (25th August 2018) - Berg, Daniela; Adler, Charles H.; Bloem, Bastiaan R.; Chan, Piu; Gasser, Thomas; Goetz, Christopher G.; Halliday, Glenda; Lang, Anthony E.; Lewis, Simon; Li, Yuan; Liepelt‐Scarfone, Inga; Litvan, Irene; et al.
ABSTRACT: Background : In 2015, the International Parkinson and Movement Disorder Society published clinical diagnostic criteria for Parkinson's disease (PD). Although recent validation studies suggest high accuracy, one unmet need is for highly specific criteria for clinical trials in early/de novo PD. Objectives : The objective of this study was to generate and test a PD diagnostic criteria termed "clinically established early PD." Methods : We modified the Movement Disorder Society criteria to increase specificity for early PD by removing all disease duration components and changing red flags to absolute exclusions. We then estimated the sensitivity/specificity of clinically established early PD criteria in patients with disease duration <5 years, selected from a 626‐patient validation study. Results : After documentation of parkinsonism, 18 individual exclusion criteria are assessed that preclude the diagnosis of "clinically established early PD." Among 212 PD and 152 non‐PD patients, the estimated specificity was 95.4%, with 69.8% sensitivity. Conclusions : We describe high‐specificity criteria for de novo PD, which are freely available for use in clinical trials. © 2018 International Parkinson and Movement Disorder Society